Postcolonial control of Fiji soccer and the return of subjugated knowledges: From the 1970s to the 2010s - Kieran E. James; Henry D. Tuidraki; Sheikh Ali Tanzil (Frontiers Media S.A., 2022)
The primary aim of this article is to use Foucault's idea of subjugated knowledges to search out areas and viewpoints within Fiji soccer which are suppressed by the governing authorities. To fulfill this aim, we explore and assess, via ethnographic research, the racial and ethnic aspects of Fiji soccer, from the 1970s to the 2010s, and how cultural hegemony facilitates continued Fiji Indian control and dominance within the sport. Next, and although we note the positive dimension of Fiji Football Association's 2014 Veterans' Dinner, we suggest that some ex-Ba players were apparently discriminated against by, puzzlingly, not being invited. The regulator was also unaware of, or insensitive to, ex-players' transportation needs as some were poor or invalid. We then look at the cases of Sweats Soccer Club (SSC) and Nadi Legends Football Club (NLFC) to show how, in the face of the regulator's indifference to the financial plight of an Indigenous village club (SSC), the ex-Nadi players set up instead a self-help organization (NLFC) to assist and encourage ex-players going through hard times. The latter was a cross-ethnic group/cross-class collaboration between ex-officials and ex-players and was largely outside the regulator's sphere of interest or intent.